2014
DOI: 10.1063/1.4901937
|View full text |Cite
|
Sign up to set email alerts
|

Power regulation and electromigration in platinum microwires

Abstract: We introduce a new experimental setup with a biasing circuit and computer control for electrical power regulation under reversing polarity in Pt microwires with dimensions of 1×10 μm(2). The circuit is computer controlled via a data acquisition board. It amplifies a control signal from the computer and drives current of alternating polarity through the sample in question. Time-to-failure investigations under DC and AC current stress are performed. We confirm that AC current stress can improve the life time of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The subscript i denotes the material, being Au or Pt. All these current densities are below the critical current densities for Au and Pt, which are around 10 10 A m −2 [57] and 10 11 A m −2 [58], respectively. Therefore, any possible combination of heater width and heater spacing will give a resistive that can withstand its operation.…”
Section: Resistive Heater Structure Designmentioning
confidence: 85%
“…The subscript i denotes the material, being Au or Pt. All these current densities are below the critical current densities for Au and Pt, which are around 10 10 A m −2 [57] and 10 11 A m −2 [58], respectively. Therefore, any possible combination of heater width and heater spacing will give a resistive that can withstand its operation.…”
Section: Resistive Heater Structure Designmentioning
confidence: 85%
“…In our research on electromigration and the time-tofailure of Pt microheaters, we have observed a gradual decrease with time in R, when microheaters are excited by electric current at constant power 23 . We know from previous work that such changes in R do not affect the thermal impedance dT /dP as this is governed by the thermal properties of the surroundings, most importantly the substrate's thermal conductivity 21 .…”
Section: Introductionmentioning
confidence: 81%
“…We subject our microheaters to a high current density, and wait until they eventually fail due to electromigration, in order to test their time-tofailure. By switching the current polarity at a frequency of f = 20 kHz (referred to as AC current stress in the article) we observed on the order of 10 3 -fold increase in the time-to-failure of our heaters, compared to when they are biased at the same power level at DC 23 . Depending on the bias, our measurements can take quite some time, the longest measurement on a single heater lasted for over a week.…”
Section: Sample Propertiesmentioning
confidence: 90%
“…In the literature, several process variables have been considered to control and monitor the electromigration process in different devices, such as dr/dt, 15,16 (dr/dt)/r, 11,17 d(1/r)/dt, 6,18 or P r , 19 with r and P r as the resistance of and the dissipated power in the device, respectively. Although all these variables are related to the speed of electromigration, a solid motivation for the particular selected process variable is lacking in most references.…”
Section: Conceptual Description Of Electromigrationmentioning
confidence: 99%